2022
DOI: 10.3390/ph15111401
|View full text |Cite
|
Sign up to set email alerts
|

A SERPINE1-Based Immune Gene Signature Predicts Prognosis and Immunotherapy Response in Gastric Cancer

Abstract: Immune checkpoint inhibitors (ICIs) therapy has been successfully utilized in the treatment of multiple tumors, but only a fraction of patients with gastric cancer (GC) could greatly benefit from it. A recent study has shown that the tumor microenvironment (TME) can greatly affect the effect of immunotherapy in GC. In this study, we established a novel immune risk signature (IRS) for prognosis and predicting response to ICIs in GC based on the TCGA-STAD dataset. Characterization of the TME was explored and fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…The SERPINEs were significantly related to patient survival of some cancers. Besides, SERPINE1 was a detrimental factor in HNSC, STAD, LUSC, CESC, SARC, PAAD, KIRP, LUAD, which was consistent in different databases and was consistent with most previous studies (Guo et al, 2022;Hong et al, 2022;Minemura et al, 2022;Xu et al, 2022;Zhou et al, 2022;Wang et al, 2023;Zhai et al, 2023). We also found that the overexpression of SERPINE2 was significantly associated with worse OS in MESO, BLCA, and LIHC.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The SERPINEs were significantly related to patient survival of some cancers. Besides, SERPINE1 was a detrimental factor in HNSC, STAD, LUSC, CESC, SARC, PAAD, KIRP, LUAD, which was consistent in different databases and was consistent with most previous studies (Guo et al, 2022;Hong et al, 2022;Minemura et al, 2022;Xu et al, 2022;Zhou et al, 2022;Wang et al, 2023;Zhai et al, 2023). We also found that the overexpression of SERPINE2 was significantly associated with worse OS in MESO, BLCA, and LIHC.…”
Section: Discussionsupporting
confidence: 92%
“…Pei et al developed a hypoxia risk score model based on SERPINE1 revealing the correlation between hypoxia and tumor immune microenvironment ( Pei et al, 2021 ). In addition, numerous studies published in the past few decades reported that SERPINE1 is one of the most reliable biomarkers and prognostic markers in many cancer types, including breast cancer ( Harbeck et al, 2004 ; Palmirotta et al, 2009 ; Duffy et al, 2014 ; Duffy et al, 2016 ; Jevrić et al, 2019 ), ovarian cancer ( Mashiko et al, 2015 ; Nakatsuka et al, 2017 ), renal cell carcinoma ( Ahluwalia et al, 2021 ), head and neck squamous cell carcinoma ( Pavón et al, 2015 ; Guo et al, 2022 ; Zhou et al, 2022 ; Li et al, 2023 ), bladder cancer ( Chan et al, 2017 ), colorectal cancer ( Sakakibara et al, 2005 ), gastric cancer ( Khan et al, 2022 ; Xu et al, 2022 ) and non-small cell lung cancers ( Sotiropoulos et al, 2019 ). Previous studies also demonstrated that SERPINE1 can promote cancer progression and metastasis as it is promoting the tumor migration, invasion, and angiogenesis ( Dellas and Loskutoff, 2005 ; Li et al, 2018 ; Kubala and DeClerck, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…SERPINE1 gene has been studied in a variety of human cancers, including gastric cancer. One group reported a SERPINE1-based immune gene signature, which can predict immunotherapy response and patient prognosis in gastric cancer 60 . Another group uncovered that SERPINE1 enhanced malignant progression and associated with poor prognosis in gastric cancer patients 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Although direct links between SNV mutations in these risk genes and GC progression warrant further independent exploration, our findings suggest their plausible roles in GC advancement. Notably, recent investigations have constructed gene signatures derived from genomic instability, with SERPINE1, among others, predicting GC prognosis [31]. Further correlational analyses between these five genes and 39 pathways unveiled distinct pathway signatures for protective and risk genes.…”
Section: Discussionmentioning
confidence: 99%